2018
DOI: 10.5897/ajb2018.16427
|View full text |Cite
|
Sign up to set email alerts
|

Studies on enhanced African black soap from Theobroma cacao (cocoa) and Elaeis guineensis (palm kernel oil)

Abstract: The indigenous African organic soap is formed by saponification. Using the local and ancient method, with slight modifications, palm kernel oil (Elaeis guineensis) and the filtrate of burnt cocoa pod ash (Theobroma cacao) were used to prepare African black soap (C 11 H 23 COO -K + ). The prepared black soap was thereafter divided into five parts. Part A was the control without additives, while parts B, C and D were enhanced with aloe vera, camwood and lime respectively. Part E was enhanced with both shea butte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…This might be due to the fear that the soap can be denatured through the addition of other chemicals. The finding is against Ikotun et al (2018) who experimentally confirmed that modification of black-soap does not denature it chemically, but rather, aided its antibacterial activities. Unfortunately, some industrial soap makers have hijacked black soap enterprise at this stage to produce well packaged refined black soap (such as dudu osun) sold for higher prices.…”
Section: Value Addition Stagementioning
confidence: 91%
See 2 more Smart Citations
“…This might be due to the fear that the soap can be denatured through the addition of other chemicals. The finding is against Ikotun et al (2018) who experimentally confirmed that modification of black-soap does not denature it chemically, but rather, aided its antibacterial activities. Unfortunately, some industrial soap makers have hijacked black soap enterprise at this stage to produce well packaged refined black soap (such as dudu osun) sold for higher prices.…”
Section: Value Addition Stagementioning
confidence: 91%
“…While traditional recipes are free from additives like dyes, fragrances, and others, scientific innovations have led to the modification of the soap through the addition of different naturally occurring beauty enhancing organic compounds like aleovera, camwood, lime, honey and shea butter. Chemical analyses of the modified black-soap samples revealed that the addition of these naturally beautifying compounds to the soap has not denatured it chemically, but rather it has aided its antibacterial activities (Ikotun et al, 2018). It was further observed that the addition of naturally occurring organic compounds to black-soap improved its deep cleansing ability, skin moisturizing effect and facilitated its ability to destroy some of the microorganisms better than the one without additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation